Darwin on stage: evolutionary theory in the theatre - Shepherd-Barr, K (Maney Publishing, 2008)
The year 2009 promises to be for Darwin what the year 2005 was for Einstein: the Darwin Year celebrates the bicentennial of Darwin's birth as well as the hundred and fiftieth anniversary of the publication of On the Origin of Species. These events will generate worldwide discussions, reflections and commemorations over a wide range of fields that Darwin's work has affected and influenced, as well as new books and biographies and retrospectives; one major series of celebrations, for example, is planned in Cambridge in July 2009 (www.darwin2009.cam.ac.uk). In the world of the arts, Darwin is providing rich source material, not least for the theatre: already several Darwin plays have emerged that demonstrate the timeliness and fascination of both the man and his work. The following review looks at some of these plays in the context of the history of the representation of Darwin's ideas in the theatre, and asks: what is it that playwrights and audiences find so theatrically engaging about Charles Darwin and evolutionary theory?